Respuesta :

Simplifying
x + 6 = 3x + -14

Reorder the terms:
6 + x = 3x + -14

Reorder the terms:
6 + x = -14 + 3x

Solving
6 + x = -14 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
6 + x + -3x = -14 + 3x + -3x

Combine like terms: x + -3x = -2x
6 + -2x = -14 + 3x + -3x

Combine like terms: 3x + -3x = 0
6 + -2x = -14 + 0
6 + -2x = -14

Add '-6' to each side of the equation.
6 + -6 + -2x = -14 + -6

Combine like terms: 6 + -6 = 0
0 + -2x = -14 + -6
-2x = -14 + -6

Combine like terms: -14 + -6 = -20
-2x = -20

Divide each side by '-2'.
x = 10

Simplifying
x = 10

Answer:

Answer is 5

Step-by-step explanation: